2021
DOI: 10.3897/bdj.9.e77464
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist to the biodiversity data of ladybeetles (Coleoptera: Coccinellidae) of the Azores Archipelago (Portugal)

Abstract: A recently-published review from 2021 presents a comprehensive checklist of ladybeetles of Portugal, including the Azores and Madeira Archipelagos. Until then, the available information was very scattered and based on a single revision dating back to 1986, a few international catalogues and databases, individual records and studies on communities of agroecosystems. However, no information was available on faunal composition across the Azorean islands and their habitats, using standardised inventories. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A large number of new records for the islands are based on recently published articles (e.g. Stüben and Borges (2019) , Carvalho et al (2021) , Costa and Borges (2021) , Marcelino et al (2021) , Soares et al (2021) , Tsafack et al (2021) , Borges et al (2021) , Borges et al (2022a) , Borges et al (2022b) , Lhoumeau et al (2022a) , Lhoumeau et al (2022b) ) and one currently in evaluation (e.g. Boieiro et al (2022) ).…”
Section: General Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of new records for the islands are based on recently published articles (e.g. Stüben and Borges (2019) , Carvalho et al (2021) , Costa and Borges (2021) , Marcelino et al (2021) , Soares et al (2021) , Tsafack et al (2021) , Borges et al (2021) , Borges et al (2022a) , Borges et al (2022b) , Lhoumeau et al (2022a) , Lhoumeau et al (2022b) ) and one currently in evaluation (e.g. Boieiro et al (2022) ).…”
Section: General Descriptionmentioning
confidence: 99%
“…For taxonomic consistency, we evaluated specific data for: Araneae , expert revision by PC and LC using the R package arakno ( Cardoso and Pekár 2022 ) that feeds on the World Spider Catalogue ( World Spider Catalog 2022 ); Coleoptera , Staphylinidae (expert revision by VA and MS; see also Borges et al (2022a) ); Coleoptera , Coccinellidae (expert revision by AOS, see also Soares et al (2021) ), Coleoptera , Curculionidae ( Stüben and Borges 2019 ) and Lepidoptera (expert revision by VV and OK).…”
Section: General Descriptionmentioning
confidence: 99%
“…- Four beetles ( Coleoptera ), Clitostethus arcuatus (Rossi, 1794) (introduced), Dryops algiricus (Lucas, 1846) (native non-endemic), Notothecta dryochares (Israelson, 1985) (endemic) and Scymnus suturalis Thunberg, 1795 (introduced). C. arcuatus and S. suturalis are ladybeetles ( Coccinellidae ) widespread in Azores ( Soares et al 2021 ). Notothecta dryochares ( Staphylinidae ) is the most abundant endemic rove-beetle in Azores ( Borges et al 2022a ), commonly found associated with the canopy and trunks of endemic trees.…”
Section: Additional Informationmentioning
confidence: 99%